Recent advances of anti-angiogenic inhibitors targeting VEGF/VEGFR axis - Wang, Lei; Liu, Wang-Qing; Broussy, Sylvain; Han, Bingnan; Fang, Hongming (Frontiers in Pharmacology, 2024)
Abbreviations: anaplastic thyroid cancer (ATC), angiopoietin-2 (Ang-2), breast cancer (BC), chronic lymphocytic leukemia (CLL), colorectal cancer (CRC), diabetic retinopathy (DR), differentiated thyroid carcinoma (DTC), diabetic macular edema (DME), endothelial cells (ECs), epidermal growth factor (EGF), fibroblast growth factor (FGF), gastro-esophageal junction (GEJ), gastrointestinal stromal tumor (GIST), glioblastoma multiforme (GBM), hepatocellular carcinoma (HCC), lymphangioleiomyomatosis (LAM), neovascular age-related macular degeneration (nAMD), neuropilins 1 and 2 (NRP1 and NRP2), non-small-cell lung cancer (NSCLC), ovarian cancer (OC), placental growth factor (PlGF), platelet-derived growth factor (PDGF), receptor tyrosine kinases (RTKs), renal cell carcinoma (RCC), retinal vein occlusion (RVO), retinopathy of prematurity (ROP), small cell lung cancer (SCLC), soft-tissue sarcoma (STS), transforming growth factor (TGF), tyrosine kinase (TK), vascular endothelial growth factor (VEGF).